2017
DOI: 10.1016/j.bbabio.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CpSRP54 function leads to a truncated light-harvesting antenna size in Chlamydomonas reinhardtii

Abstract: The Chlamydomonas reinhardtii truncated light-harvesting antenna 4 (tla4) DNA transposon mutant has a pale green phenotype, a lower chlorophyll (Chl) per cell and a higher Chl a/b ratio in comparison with the wild type. It required a higher light intensity for the saturation of photosynthesis and displayed a greater per chlorophyll light-saturated rate of oxygen evolution than the wild type. The Chl antenna size of the photosystems in the tla4 mutant was only about 65% of that measured in the wild type. Molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 62 publications
0
48
0
Order By: Relevance
“…The truncated, light-harvesting antennae are photosynthetically more productive under high-light and high-density culture conditions than cultures with fully pigmented cells. This improvement is due to alleviation of over-absorption, and dissipation of excess energy by the outer layer of cells in the culture, resulting in improved light penetration deeper into the culture and culture productivity [34,35]. Our results showed that mp3 could be considered as an antenna mutant.…”
Section: Discussionmentioning
confidence: 92%
“…The truncated, light-harvesting antennae are photosynthetically more productive under high-light and high-density culture conditions than cultures with fully pigmented cells. This improvement is due to alleviation of over-absorption, and dissipation of excess energy by the outer layer of cells in the culture, resulting in improved light penetration deeper into the culture and culture productivity [34,35]. Our results showed that mp3 could be considered as an antenna mutant.…”
Section: Discussionmentioning
confidence: 92%
“…Cas9-mediated gene knock-out has been reported for several genes and the use of donor DNA with RNP, called knock-in, has emerged recently. However, the gene-editing efficiency reported in previous studies was not satisfactory (Shin et al, 2016;Greiner et al, 2017;Jeong et al, 2017a).…”
Section: Discussionmentioning
confidence: 93%
“…This nonhomogeneous light penetration results in a low productivity of the system, the inner layers being almost in the dark [21]. Mutant strains with reduced pigment content per cell resulting either from a truncated antenna size or a lower overall density of photosynthetic units per cell were reported for different species, as C. reinhardtii, C. vulgaris, C. sorokiniana and N. gaditana, being characterized by an increased productivity [22][23][24][25]. In addition, up to 80% of the light absorbed by the external layers is dissipated as heat by the activation of photoprotective processes, with consequent loss of light use efficiency and biomass productivity [26].…”
mentioning
confidence: 99%